Delayed risk in individual and social decisions - Özgümüs, Asri; Rau, Holger A.; Trautmann, Stefan T. (Journal of economic psychology, 2024)
This paper studies temporal-distance effects on individual and social risks, testing Construal Level Theory. We elicit WTPs for risky and ambiguous lotteries and vary the timing (immediately vs. in two weeks) when the uncertainty is resolved. Subjects have lower WTPs for longshots than for safer lotteries. Under ambiguity, this gap decreases with temporal distance. Subjects are ambiguity averse, which becomes less pronounced when low-probability lotteries are processed in the future. In a trust game, we study temporal-distance effects on social risks. Time distance lowers trust as trustors correctly anticipate that reciprocity is lower when trustees decide in the future.